Semicondutores no ensino médio: uma proposta de ensino de física contemporânea - Freitas, Frederico Campos (Universidade Federal de São Carlos, 2013)
Most of electronic devices use diodes and transistors based on semiconductors. For a people better relationship and understanding these technologies, is important to know some basic principles in what these devices are based. There are several official documents and academic researches related with this theme, always exalting of the need teach concepts of Modern Physics - especially those related to Quantum theory - for high school students. The goal of this work was the production of four short videos, whose intention was explain semiconductor concepts for high school students. In this master thesis is described the process of screenplay s production, videos recording and its presentation on two classes of High School last grade of a private school in Uberaba-MG. After each video s presentation, a questionnaire with Likert s items was given to students for measure their attitude with reference to the concepts presented in these four videos. The questionnaires results were analyzed from theory point of view, and the proposed goal has been achieved.
Keywords: Física estudo e ensino; Física moderna e contemporânea; Semicondutores; Recursos audiovisuais; Vídeos para ensino; CIENCIAS EXATAS E DA TERRA